2012
DOI: 10.1021/cg3010135
|View full text |Cite
|
Sign up to set email alerts
|

Guest Driven Structural Correlations in DPDS [Di(4-pyridyl)disulfide]-Based Coordination Polymers

Abstract: Three novel coordination polymers have been obtained by the reaction of M(NO 3 ) 2 ·6H 2 O (M = Mn II and Co II ) or FeCl 2 ·4H 2 O with KNCS and DPDS [di(4-pyridyl)disulfi de] l igand, [Mn-(NCS) 2 (DPDS) 2 ] 2 ·DPDS·H 2 O (1), [Fe(NCS) 2 (DPDS) 2 ]·3H 2 O (2), and [Co(NCS) 2 (DPDS) 2 ]·2H 2 O (3). The three complexes exhibit infinite linear chain structures, where the metal ions are connected by double N,N′-DPDS bridges, that are further connected through hydrogen bonding to give pseudo-3D structures which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The structure of 1 D‐DS‐Co‐MOF ( M w =652 g mol −1 , Figure (a)) featured a one‐dimensional chain parallel to the c ‐axis and comprising Co 2+ ions, monodentate NCS ligands in the equatorial position, and bidentate 4dpds ligands in the axial position . The chain formed a unit cell with eight H 2 O molecules per pore, attributable to hydrogen bonding between the pyridine moieties of 4dpds and NCS ligands, whereas PLATON calculations on crystal structures after solvent removal suggested that the pore size equaled 452 Å 3 per unit cell volume or 15 % of the total crystal volume.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of 1 D‐DS‐Co‐MOF ( M w =652 g mol −1 , Figure (a)) featured a one‐dimensional chain parallel to the c ‐axis and comprising Co 2+ ions, monodentate NCS ligands in the equatorial position, and bidentate 4dpds ligands in the axial position . The chain formed a unit cell with eight H 2 O molecules per pore, attributable to hydrogen bonding between the pyridine moieties of 4dpds and NCS ligands, whereas PLATON calculations on crystal structures after solvent removal suggested that the pore size equaled 452 Å 3 per unit cell volume or 15 % of the total crystal volume.…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we report the relationship between the structural characteristics and battery performance of DS‐MOFs featuring diverse structures and containing various disulfide ligands with flexible S−S bonds. In particular, we focus on the relationships between (1) porosity and battery capacity, and (2) structural dimensionality (1 D, 2 D, and 3 D) and cycling performance, by using three porous DS‐MOFs, namely 1 D‐DS‐Co‐MOF ([Co(NCS) 2 (4dpds) 2 ] ⋅ 2 H 2 O), 2 D‐DS‐Cu‐MOF ([Cu(C 2 O 4 ) 2 (4dpds)] ⋅ 6 H 2 O), 3 D‐DS‐Mn‐MOF ([Mn 2 (H 2 O) 2 (6dtna) 2 ] ⋅ 4 CH 3 OH ⋅ H 2 O), and two nonporous coordination polymers (DS‐CPs), viz. 1 D‐DS‐Cu‐CP ([Cu 4 (HCO 2 ) 6 (OH) 2 (4dpds) 2 ] ⋅ 2 CH 2 Cl 2 ) and 3 D‐DS‐Mn‐CP ([Mn 5 (OH) 2 (2 Dtba) 4 ]) …”
Section: Introductionmentioning
confidence: 99%
“…The structure of 1D-DS-Co-MOF (M w = 652 gmol À1 ,F igure 1(a)) featured ao ne-dimensional chain parallel to the caxis and comprising Co 2 + ions, monodentate NCS ligands in the equatorial position, and bidentate 4dpds ligandsi nt he axial position. [29] The chain formed au nit cell with eight H 2 O molecules per pore, attributable to hydrogen bonding between the pyridine moieties of 4dpds and NCS ligands, where-as PLATON calculations [35] on crystal structures after solventr emovals uggested that the pore size equaled 452 3 per unit cell volumeo r15 %o ft he total crystal volume. To utilize these pores for electrolyte ion intercalation, we evaporated guest molecules under vacuum.T GA ( Figure S1 (a) in the Supporting Information) revealed that compared with the vacuum-dried sample, the as-prepared one showeda3.1 %w eightl oss at 40-150 8C, whereas PXRD analysisd emonstrated that the MOF structure wasretained after vacuum-drying ( Figure S1 (b) in the Supporting Information).…”
Section: Resultsmentioning
confidence: 98%
“…1D-DS-Co-MOF ([Co(NCS) 2 (4dpds) 2 ]·2 H 2 O): [29] An aqueous solution (10.0 mL) of KNCS (1.00 mmol) and Co(NO 3 ) 2 ·6H 2 O( 0.250 mmol) was added to methanolic 4dpds (0.250 mmol, 10.0 mL) to afford a pink precipitate, which was washed with deionized water (5 3mL).…”
Section: Syntheses Of Ds-mofs and Ds-cpsmentioning
confidence: 99%
See 1 more Smart Citation